Factors That Influence Sustainability Environmental Dimension: A Methodological Framework Approach - Ionuț Viorel HERGHILIGIU; Ioan-Bogdan ROBU; Adrian VILCU (Communications of International Proceedings, 2021)
Businesses which have concerns regarding sustainable development assumes its characteristic dimensions. One of this sustainability dimensions is the environmental one. This important dimension integrates an associated shift in business philosophy that provide “instruments” to achieve environmental goals. The worldwide managerial instrument considered to be a driving force to a sustainable organizational development is Environmental management system (EMS). Hence the paper aims to propose a theoretical framework that could identify and asses the factors that influence sustainability environmental dimension. This methodological framework can serve to practitioners as a tool in order have a holistically approach regarding the environmental issue.
Keywords: Methodological Approach; Influence Factors; Statistical Correlation Analysis; EMS.